Structural Anthropology and the "Death of Man" - Švec, Ondřej (Teorie vědy / Theory of Science, 2009)
According to the traditional interpretation, Lévi-Strauss’ structural anthropology deposes the concept of man and the notion of human nature from its central place in human and social sciences. While it’s necessary to acknowledge Lévi-Strauss’ distance vis-à-vis all philosophy based on intentionality, experience and consciousness of subject, we argue that the most interesting purpose of the structural anthropology lies elsewhere. Not only Lévi-Strauss never declared himself being part of anti-humanism movement, but most of all, his famous polemics with Sartre at the end of La Pensée sauvage should be interpreted as part of his fight against ethnocentrism. The project of “dissolving the man” can be thus read as deconstructing the idea that western man makes of himself in the light of ethnological findings about universal structures orchestrating all human societies. We further show that the notion of subject survived its very death announced by the most radical structuralist thinkers and that structural method could be effectively employed in order to study different techniques and modes of subjectivation, revealing that “becoming subject” is a process structured by our language, symbolic universe and ethical teleology.